2022
DOI: 10.3390/jcm11154526
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Classification Results Accuracy for CT Soft Tissue and Bone Reconstructions in Detecting the Porosity of a Spongy Tissue

Abstract: The aim of the study was to compare the accuracy of the classification pertaining to the results of two types of soft tissue and bone reconstructions of the spinal CT in detecting the porosity of L1 vertebral body spongy tissue. The dataset for each type of reconstruction (high-resolution bone reconstruction and soft tissue reconstruction) included 400 sponge tissue images from 50 healthy patients and 50 patients with osteoporosis. Texture feature descriptors were calculated based on the statistical analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“… To create an implant model, the initial data were sets of tomographic slices (DataSets), performed with a fixed pitch of 1 mm (see Fig. 1) 10,11,12 .  The task of creating an implant model using rapid prototyping tools according to spiral computed tomography consists of 6 main stages:  segmentation -the selection on the images of tomographic sections of bone structures;  determine the location and selection of the bone defect replacement method;  creation of a large implant reconstruction;  preparation of data for prototyping in stl format;  creating a layer-by-layer model of the implant in the G-code format for 3D printing on specific equipment.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“… To create an implant model, the initial data were sets of tomographic slices (DataSets), performed with a fixed pitch of 1 mm (see Fig. 1) 10,11,12 .  The task of creating an implant model using rapid prototyping tools according to spiral computed tomography consists of 6 main stages:  segmentation -the selection on the images of tomographic sections of bone structures;  determine the location and selection of the bone defect replacement method;  creation of a large implant reconstruction;  preparation of data for prototyping in stl format;  creating a layer-by-layer model of the implant in the G-code format for 3D printing on specific equipment.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Soft tissue reconstruction images were used for the research. The research showed that the images derived from soft tissue reconstruction allow obtaining more accurate values of texture parameters, increasing the accuracy of classification, and offering better possibilities for diagnosing osteoporosis [ 33 ]. From the series of images, the sample sections showing the inside of the circle with the spongy essence were selected ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%